The Current Status and Future Prospects of Corporate e-Learning in Korea - Lim, Cheolil (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
Corporate e-Learning in Korea has grown rapidly over the previous six years (2000-2005). This study argues that the main cause of this heightened interest in corporate e-Learning in Korea was not that companies needed to provide high-quality training programs through the Internet, but rather that the government took initiative to transform the state into an information-based society. The policies for quantitative growth with minimum levels of quality and uniformity have been dominant and have resulted in the lack of diverse e-Learning types for authentic practices in workplaces. This paper suggests that in order to cope with the new competency requirements of employees, corporate e-Learning should be guided both by governmental support and by company initiative.